Tinjauan Atas Prosedur Pengajuan Hingga Pembayaran Klaim Asuransi Kendaraan Bermotor : Studi Kasus Pada PT Asuransi Jasaraharja Putera Kantor Pemasaran Bogor - Annur, Syarah Zahira; Roup, Abdul (Program Vokasi dan LPPM IBI Kesatuan, 2024)
The development of the number of vehicles is inseparable from the risk of uncertainty that lurks. Therefore, motor vehicle insurance is present as a place to transfer risk from unexpected things that happen to vehicles, or to parties included in the policy. The accounting information system exists because of the need to monitor business activities. In submitting an insurance claim, a procedure is needed regarding the claim submission flow to facilitate the company and monitor the company's performance. The purpose of this review is to determine the application of the system in the procedure for submitting to paying JP-Astor claims. This research was conducted by the author at PT. Asuransi Jasaraharja Putera Bogor Marketing Office located at Jl. Re. Martadinata Komp. Ruko Sentra Air Mancur No. 2h, Bogor Tengah, Bogor City. The results of the review indicate that PT Asuransi Jasaraharja Putera Bogor Marketing Office has been quite good at carrying out the procedure for submitting to paying JP-Astor claims. The claim submission and claim payment system at Jasaraharja Putera Bogor Marketing Office has helped the work of employees and insured parties, so that they know the extent of the claim process that has been submitted. Accounting Information System implemented through Care System helps companies in registering and remote authorization. Keywords: Submission, Payment, Claim, Motor Vehicle